Spatial and temporal variability in fish diversity of Vellar Estuary (South East Coast of India) - Murugan, S.; Khan, Ajmal; Lyla, P.S.; Manokaran, S.; Raja, S.; John, Akbar (SCIENCEDOMAIN International, 2014)
Aim: The present study describes spatial and seasonal changes in fish species composition of 3 zones in Vellar estuary. Sample: The95 species of finfishes recorded here (bony fishes 93 species and elasmobranchs 2 species) included 8 freshwater species, 9 estuarine species, 63 estuarine and marine species and 13 marine species. Results: The number of species and diversity (Shannon-Wiener index, Margalef richness index, average taxonomic distinctness index and the total phylogenentic diversity index) decreased from the marine zone towards freshwater zone. Cluster analysis showed gradual change in species composition from the marine zone to the freshwater zone of the estuary. ANOSIM showed significant seasonal changes (Global R=-0.93; P=0.1%). Pair wise comparison between the seasons also showed significant differences except between post monsoon and summer. However the differences between the zones were not significant. Conclusion: The higher diversity values and V statistics indicated the healthy nature of the estuary. - See more at: http://www.sciencedomain.org/abstract.php?iid=463&id=32&aid=4066#.U88b5D-SwRE